2019
DOI: 10.1155/2019/2859637
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Antileishmanial Activity of Certain Quinoline-4-carboxylic Acids

Abstract: Leishmaniasis is a fatal neglected parasitic disease caused by protozoa of the genusLeishmaniaand transmitted to humans by different species ofphlebotominesandflies. The disease incidence continues to increase due to lack of vaccines and prophylactic drugs. Drugs commonly used for the treatment are frequently toxic and highly expensive. The problem of these drugs is further complicated by the development of resistance. Thus, there is an urgent need to develop new antileishmanial drug candidates. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
7
0
1
Order By: Relevance
“…Noteworthy, L. donovani DHODH has explicitly been proposed as a target for 2‐aryl‐4‐quinolinecarboxylic acids. [ 23 ] By aligning the 3D structures of T. cruzi , L. major , and human DHODH active sites, it can be seen that, despite the substitution of some residues, the profile of interactions for molecular recognition is highly conserved between the two classes. [ 44 ] Furthermore, human DHODH inhibitors included brequinar (synthetic 4‐quinolinecarboxylic acid) and several series of 4‐quinolinecarboxylic acid derivatives, [ 45 ] also with antiviral activity, [ 46 ] strongly suggesting the active compounds 4 and 5 as Leishmania DHODH inhibitors, based on these reported data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, L. donovani DHODH has explicitly been proposed as a target for 2‐aryl‐4‐quinolinecarboxylic acids. [ 23 ] By aligning the 3D structures of T. cruzi , L. major , and human DHODH active sites, it can be seen that, despite the substitution of some residues, the profile of interactions for molecular recognition is highly conserved between the two classes. [ 44 ] Furthermore, human DHODH inhibitors included brequinar (synthetic 4‐quinolinecarboxylic acid) and several series of 4‐quinolinecarboxylic acid derivatives, [ 45 ] also with antiviral activity, [ 46 ] strongly suggesting the active compounds 4 and 5 as Leishmania DHODH inhibitors, based on these reported data.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, we found a hit compound with antimalarial and antichagasic (Chagas diseases caused by the protozoan Trypanosoma cruzi ) activities and four derivatives with moderate activity against Leishmania (Leishmania) infantum chagasi and L. donovani (Figure 1). Furthermore, 2‐methyl and 2‐aryl‐4‐quinolinecarboxylic acids [ 23 ] and 4‐amino‐2‐styrylquinolines [ 24 ] with antileishmanial activity were recently reported. All these findings prompted us to investigate the influence on the antileishmanial activity of the vinyl‐bridge insertion between the 2‐aryl ring and the quinoline core of these new 4‐quinolinecarboxylic acids.…”
Section: Introductionmentioning
confidence: 99%
“…In the beginning of 2019, Abdelwahid et al synthesized a series of fifteen quinoline-4-carboxylic acids and evaluated them for its potential as antileishmanial agents against L. donovani promastigotes [ 54 ]. The results demonstrated that, from this entire series of derivatives, five derivatives present moderate to weak antileishmanial activities, with IC 50 values ranging from 75.46 µM to 313.86 µM.…”
Section: Quinolines As Antileishmanial Agentsmentioning
confidence: 99%
“…e axenic standard L. infantum, L. tropica, and L. major promastigotes were used in the study. e promastigotes were propagated on RPMI-1640 medium and maintained by passaging [33,34]. Promastigotes were washed with phosphate buffered saline (PBS).…”
Section: Antileishmanial Activitymentioning
confidence: 99%